2008
DOI: 10.1292/jvms.70.993
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Plasma Circulating mRNA as a Marker to Detect Hepatic Injury

Abstract: ABSTRACT. Utility of plasma circulating mRNA as a molecular marker to detect hepatic injury was evaluated. Total RNA was isolated from plasma of the rat liver fibrosis models at various time points, and plasma circulating mRNAs of major liver-derived genes, albumin and haptoglobin, were measured by real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). Sensitivity and kinetics of plasma circulating mRNA were compared with those of plasma alanine aminotransferase (ALT) activity. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Recently, a study was performed that measured the level of gene expression of haptoglobin ( Hp ) in blood and compared it to serum ALT as a marker of liver damage 28 . The group found that Hp gene expression was more sensitive as an indicator of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study was performed that measured the level of gene expression of haptoglobin ( Hp ) in blood and compared it to serum ALT as a marker of liver damage 28 . The group found that Hp gene expression was more sensitive as an indicator of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma circulating albumin mRNA may serve as a molecular marker for hepatic injury using the acute and chronic rat liver fibrosis models [20]. The measurement of plasma circulating albumin mRNA enabled sensitive and early detection of hepatic injury with a large assay window compared with that of plasma ALT activity.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have had a mixed level of success, however, with detection rates of blood ALB mRNA of >100% from patients with HCC [19], cirrhosis, or hepatitis and from healthy controls. The correlation of plasma ALB mRNA concentration with hepatic injury in rats have been reported [20], however, the studies in human is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have had a mixed level of success, however, with detection rates of blood ALB mRNA of >100% from patients with HCC (Anker &Stroun 2002), cirrhosis, or hepatitis and from healthy controls. The correlation of plasma ALB mRNA concentration with hepatic injury in rats have been reported, however, the studies in human is still lacking (Kudo et al, 2008).…”
Section: ____________________________________________________________mentioning
confidence: 99%